Nonintensivist Training to Increase the Staff Capacity of Intensive Care Units During COVID-19 Pandemic Surge in Argentina. (31st August 2023) - Monteverde, Ezequiel; Bosque, Laura; Klappenbach, Roberto; Baliña, Joaquín; Lartigue, Betina; Arán, María Inés; Cano, Nicolás; Reina, Rosa; Silberman, Pedro; Ortiz, Claudio; Gutiérrez, Vicente; Neira, Jorge
Abstract: Objective: The aim of this study was to report the results of a nationwide critical-care course for non-intensivists to increase staff capacity of intensive care units (ICUs) during the coronavirus disease 2019 (COVID-19) pandemic in Argentina. Methods: Three academic organizations, with special funding from 55 private companies, developed a short virtual course comprised of Web-based videos, virtual tutorials, and a forum chat. Each state assigned scholarships to non-ICU staff from public hospitals. Students received active follow-up for the completion of the course and took a survey upon course completion. Results: After 4 m, there were 10, 123 students registered from 661 hospitals in 328 cities. Of these, 67.8% passed the course, 29.1% were still ongoing, and 3.1% were inactive. Most students were female (74.2%) with a median of 37 y old (IQR 31-44). The group was composed of 56.5% nurses, 36.2% physicians, and 7.4% physiotherapists, of whom 48.3% did not have any experience in critical care. Mean overall satisfaction was 4.4/5 (standard deviation, 0.9), and 90.7% considered they were able to apply the contents to their practice. Conclusions: This course was effective for rapid training of non-ICU personnel. The assignment strategy, the educational techniques, and the close follow-up led to low dropout and high success rates and satisfaction.